Connectedness and ICT: Opening the door to possibilities for people with intellectual disabilities. (December 2020) - Barlott, Tim; Aplin, Tammy; Catchpole, Emma; Kranz, Rebecca; Le Goullon, Damian; Toivanen, Amanda; Hutchens, Sarah
This study aimed to investigate the experiences of people with intellectual disability (ID) using information and communication technologies (ICTs) and the ways these technologies foster social connectedness. In partnership with a community mental health organization, this qualitative descriptive study explored the experiences of 10 people with ID using ICTs. Participants described how ICTs Opened the Door to Possibilities in their life – ICTs provided an avenue for connecting with other people, a means to pursue personal interests and a tool for organizing everyday life. Opening the door to possibilities was further understood as movement towards digital inclusion for people with ID, conceptualized as the fit between social opportunity and personal skills. We have identified the prominent role social supports play in creating (and constraining) opportunities for digital inclusion, and that digital inclusion has the potential to enable social connectedness and the development of agency. Consideration of the complex interaction between social opportunity and personal skills, and the mediating influence of supports, will enhance the inclusion of people with ID.